Novice physiotherapists’ perceived challenges in clinical practice in Singapore - Mary Xiaorong Chen; Meredith Tsz Ling Yeung; Nur Khairuddin Bin Aron; Joachim Wen Jie Lee; Taylor Yutong Liu (The Asia Pacific Scholar)
Introduction: Transitioning from a novice physiotherapist (NPT) to an independent practitioner presents significant challenges. Burnout becomes a risk if NPTs lack adequate support for learning and coping. Despite the importance of this transition, few studies have explored NPTs’ experiences in Singapore. This study aims to investigate the transitional journey of NPTs within this context. Methods: Conducted as a descriptive phenomenological study, researchers collected data through semi-structured online interviews with eight NPTs from six acute hospitals across Singapore. Simultaneous data analysis during collection allowed for a reflexive approach, enabling the researchers to explore new facets until data saturation. Thematic analysis was employed and complemented by member triangulation. Results: The challenges NPTs encountered include seeking guidance from supervisors, managing fast-paced work and patients with complex conditions. Additionally, NPTs grappled with fear of failure, making mistakes and self-doubt. They adopted strategies such as assuming responsibility for learning, developing patient-focused approaches, and emotional resilience. However, a concerning trend emerged with the growing emotional apathy and doubts about their professional choice. Conclusion: This study provides a nuanced understanding of the challenges faced by NPTs during their transition. The workplace should be viewed as a learning community, where members form mutual relationships and support authentic learning. Recommendations include augmenting learning along work activities, fostering relationships, ensuring psychological safety, and allowing “safe” mistakes for comprehensive learning.